Assessment of crop evapotranspiration and deep percolation in a commercial irrigated citrus orchard under semi-arid climate: combined Eddy-Covariance measurement and soil water balance-based approach - Ali, A.A.; Bouchaou, L.; Er-Raki, S.; Hssaissoune, M.; Brouziyne, Youssef; Ezzahar, J.; Khabba, S.; Chakir, A.; Labbaci, A.; Chehbouni, Abdelghani (Elsevier, 2023)
An accurate estimate of crop coefficient (Kc) values at different development stages (Kcini, Kcmid, and Kcend) is crucial for assessing crop water requirements in semi-arid regions. The objectives of this study were first to quantify the reference evapotranspiration (ETo) and to calculate the actual evapotranspiration (ETa) over citrus in a semi-arid climate under drip irrigation. For this purpose, a site of a citrus orchard in Souss-Massa, planted with the Esbal variety of clementine, was equipped with an Eddy-Covariance (EC) system, and sensors to measure radiation, soil heat flux, and micrometeorological forcing data, during 2020 and 2021 seasons. Also, the soil moisture content at various soil depths in the root zone near the EC tower was monitored. The energy balance closure (EBC) approach was adopted for flux assessment to ensure a quality check for the EC measurements. The obtained EBCs were about 82% and 79% for the daily measurements in 2020 and 2021, respectively, which can be considered acceptable considering the nature of the citrus orchard (relatively tall and sparse). Second, the study aimed to estimate actual Kc act values for citrus under the same irrigation strategy. The derived values were compared to different recommended Kc values in the literature. In the third stage, this work aimed to offer an alternative plan to sustainable irrigation management by elaborating an irrigation schedule for citrus crops in the region using the FAO-56 simple approach to avoid water stress and deep percolation (i.e., Ks = 1 and DP = 0). Eventually, an irrigation schedule was drawn following the crop’s phenological stages. The seasonal mean citrus evapotranspiration (ETa) values are 1.68, 3.02, and 1.86 mm/day for the initial, mid, and end-season. The seasonal actual Kc act values were 0.64, 0.58, and 0.64 for Kcini, Kcmid, and Kcend, respectively. Additionally, the application of the water balance equation revealed that a large quantity of water is lost through deep percolation (52% of total water supplied). The study focuses on Citrus trees being a strategic crop with important socio-economic values in the Souss-Massa region. Thus, the results should support both scientists and farmers in planning and strategy development.